Dispersion-based control of spatial modes for parametric down-conversion in a multimode waveguide - Karpiński, M; Radzewicz, C; Banaszek, K (2012)
We demonstrate a scheme to control spatial characteristics of spontaneous parametric down-converted light in a multimode waveguide, based on intermodal dispersion. The down-converted photons are characterized by measurement of beam quality factors. © 2012 OSA.